Nano zero-valent iron modified immobilized composite microbial population, and preparation method and application thereof
Patent Information
- Application Number
- CN202611141736.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-13
AI Technical Summary
然而,nZVI对污染物的完全矿化能力不足,可能导致有毒中间产物的积累
本发明将纳米零价铁负载于沸石后与PVA-SA复合水凝胶共同包埋复合菌群,nZVI的化学还原作用与微生物的酶促降解作用协同形成“化学-生物”双通道脱色路径,显著提高了染料脱色效率。固定化小球对偶氮染料的24小时脱色率可达94%以上。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to a nano-zero-valent iron modified immobilized composite microbial community, its preparation method, and its application in dye decolorization. Background Technology
[0002] Azo dyes are the most widely used synthetic dyes in the textile printing and dyeing industry. Their wastewater is characterized by high color intensity, strong biological toxicity, and stable chemical structure; direct discharge can cause serious harm to the aquatic ecosystem and human health. How to efficiently and economically treat azo dye wastewater has become a research hotspot in the field of water pollution control.
[0003] Microbial degradation methods have attracted widespread attention due to their environmental friendliness and low operating costs. However, free-living microorganisms have several limitations in practical applications: single species often can only degrade dyes with specific structures, resulting in a narrow degradation spectrum; high concentrations of dyes have toxic inhibitory effects on microorganisms; and free-living microorganisms are easily lost and difficult to recycle. To address these issues, researchers have attempted to use immobilization technology to embed microorganisms in carrier materials. Polyvinyl alcohol (PVA)-sodium alginate (SA)-zeolite composite carriers are commonly used immobilization systems. Their rich internal pore structure facilitates microbial attachment and proliferation, and the immobilized microbial communities exhibit a wider pH adaptation range, higher thermal stability, and greater tolerance. However, existing PVA-SA-zeolite immobilization systems rely solely on the enzymatic degradation of microorganisms for dye decolorization, and there is still room for improvement in decolorization efficiency.
[0004] Nano-zero valent iron (nZVI) possesses strong reducing power, enabling the chemical reduction and decolorization of azo dyes by disrupting azo bonds. However, nZVI's ability to completely mineralize pollutants is insufficient, potentially leading to the accumulation of toxic intermediates. Combining nZVI with microbial degradation holds promise for achieving a synergistic effect between chemical reduction and biodegradation; however, a mature technological solution for effectively integrating nZVI with immobilized microbial communities is currently lacking. Summary of the Invention
[0005] In view of this, the purpose of this invention is to provide a nano-zero valent iron modified immobilized composite microbial community, its preparation method and application. This invention combines the chemical reduction effect of nano-zero valent iron with the biodegradation effect of the composite microbial community to form a "chemical-biological" synergistic decolorization dual channel, which significantly improves the dye decolorization efficiency and recycling stability.
[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a nano-zero-valent iron-modified immobilized composite microbial community, comprising the following steps: S1. Nano-zero ferric iron is loaded onto zeolite to obtain nano-zero ferric iron modified zeolite; S2. Mix nano-zero-valent iron modified zeolite with polyvinyl alcohol, sodium alginate and water to prepare a carrier slurry; S3. Mix the composite bacterial culture solution with the carrier slurry to obtain the bacterial cell embedding solution; S4. The bacterial cell embedding solution is dropped into a cross-linking agent solution for cross-linking and solidification to obtain immobilized microspheres; The complex microbial community includes Serratia decoloris, Bacillus subtilis, and Pseudomonas aeruginosa. The bacterial suspensions of Serratia decoloris, Bacillus subtilis and Pseudomonas aeruginosa were mixed at a live cell count ratio of 1:(0.5-1.5):1; the OD600 of the mixed bacterial suspension was 0.7.
[0007] Preferably, the method for loading nano-zero valent iron onto zeolite in S1 is as follows: zeolite is impregnated in FeSO4 solution, and then NaBH4 is added for liquid-phase reduction to obtain nano-zero valent iron modified zeolite.
[0008] Further, the FeSO4 solution has a concentration of 0.1 mol / L, the NaBH4 solution has a concentration of 0.2 mol / L, and the NaBH4 reacts with Fe... 2+ The molar ratio is 2:1.
[0009] Furthermore, in the nano-zero-valent iron modified zeolite, the mass ratio of iron to zeolite is 1:6.
[0010] In this invention, step S1 is based on the following principle: using FeSO4·7H2O as the iron source and NaBH4 as the reducing agent, nano-zero-valent iron particles are generated in situ on the surface and within the pores of zeolite through a liquid-phase reduction reaction. The three-dimensional porous structure of zeolite provides a confined space for the generation of nZVI, effectively inhibiting the aggregation of nZVI particles, resulting in smaller particle size, more uniform dispersion, and higher reactivity of the generated nZVI. At the same time, the adsorption capacity of zeolite itself can rapidly enrich dye molecules in the early stage of decolorization, providing a high local concentration environment for subsequent chemical reduction and biodegradation.
[0011] Preferably, in the carrier slurry of S2, the mass fraction of polyvinyl alcohol is 6%~8%, the mass fraction of sodium alginate is 1%, and the mass fraction of nano-zero ferric modified zeolite is 2%.
[0012] Preferably, the volume ratio of the composite bacterial culture solution to the carrier slurry in S3 is 1:5.
[0013] Preferably, the crosslinking agent in S4 is a calcium chloride solution with a concentration of 3 wt%.
[0014] Preferably, the cross-linking curing time is 8-12 hours and the temperature is 8-12℃.
[0015] Preferably, the diameter of the immobilized microspheres in S4 is 3~5mm.
[0016] In steps S2 to S4, a large number of hydroxyl groups on the polyvinyl alcohol (PVA) molecular chain react with the carboxyl groups on the sodium alginate (SA) molecular chain in Ca2+. 2+ Cross-linking forms an interpenetrating network structure, in which Z-nZVI particles are uniformly dispersed. These particles act both as functional components providing chemical reducing power and as physical cross-linking points to further enhance the stability of the carrier structure. The bacterial cell embedding solution is added dropwise to a CaCl2 solution. 2+ Ionic crosslinking with SA forms an "eggshell structure" hydrogel, immobilizing PVA molecular chains, Z-nZVI particles, and the composite bacterial community in situ within the gel network. Low-temperature (8~12℃) crosslinking effectively avoids damage to bacterial activity caused by crosslinking exothermic reactions, while a longer crosslinking time (12 hours) ensures the gel network fully matures. The resulting immobilized microspheres have a loose and porous internal structure, which facilitates the diffusion and mass transfer of dye molecules and dissolved oxygen.
[0017] The present invention also provides a nano-zero-valent iron modified immobilized composite microbial community prepared by the above preparation method.
[0018] This invention also provides the application of the above-mentioned nano-zero-valent iron modified immobilized composite microbial community in dye decolorization.
[0019] Preferably, the dye is an azo dye.
[0020] Preferably, the azo dye is Reactive Black 5 or Methyl Orange.
[0021] Preferably, the application conditions are: dye concentration 50~200mg / L, temperature 25~35℃, pH 6~9.
[0022] It contains at least the following beneficial technical effects: This invention loads nano-zero valent iron onto zeolite and co-encapsulates a composite microbial community with a PVA-SA composite hydrogel. The chemical reduction of nZVI and the enzymatic degradation by microorganisms synergistically form a "chemical-biological" dual-channel decolorization pathway, significantly improving dye decolorization efficiency. The immobilized microspheres can achieve a decolorization rate of over 94% for azo dyes within 24 hours.
[0023] This invention uses a complex microbial community composed of Serratia decolorizing bacteria, Bacillus subtilis, and Pseudomonas aeruginosa. The three bacteria work together to not only quickly open the chromophores of the dye to achieve decolorization, but also to further mineralize the intermediate products and avoid secondary pollution.
[0024] This invention effectively protects the microbial community from the toxicity of high concentrations of dyes and adverse environments by embedding and immobilizing it with a PVA-SA-zeolite-nZVI composite carrier. The immobilized microspheres have high mechanical strength and good storage stability, and the decolorization rate remains above 90% after 15 batches of recycling.
[0025] The preparation method of this invention is simple, the operating conditions are mild, and the raw materials are readily available, which has good prospects for industrial application. Detailed Implementation
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0028] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0029] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.
[0030] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0031] Unless otherwise specified, "room temperature" and "normal temperature" in this invention refer to 25±2℃.
[0032] Unless otherwise specified, all raw materials or instruments used in the following embodiments of the present invention are commercially available.
[0033]
[0034] Example 1 This embodiment provides a method for preparing a nano-zero-valent iron-modified immobilized composite microbial community, including the following steps: 1. Activation and scale-up culture of microorganisms The purchased Serratia depigmentosus, Bacillus subtilis, and Pseudomonas aeruginosa lyophilized powders were revived according to the supplier's instructions. The revived bacterial cultures were streaked onto LB agar plates using an inoculation loop and incubated at 30°C for 24–48 hours until single colonies formed. Single colonies of each strain were picked and inoculated into 50 mL LB liquid medium (250 mL Erlenmeyer flasks) and incubated at 30°C with constant shaking at 150 rpm for 12–16 hours until the late logarithmic growth phase. The optical density (OD) of each bacterial culture at 600 nm was measured using a UV-Vis spectrophotometer. 600 ), and use sterile LB medium to measure the OD of each bacterial culture. 600 Adjust to 0.7. Mix the three bacterial solutions in a volume ratio of 1:1:1 to obtain a composite bacterial solution.
[0035] 2. Preparation of nano-zero-valent iron modified zeolite Natural clinoptilolite was ground through a 200-mesh sieve, washed three times with deionized water to remove soluble impurities, and dried at 105℃ for 12 hours for later use. 27.8 g of FeSO4·7H2O was dissolved in 1 L of deionized water to prepare a 0.1 mol / L Fe... 2+ Solution. Add the pretreated zeolite to the Fe solution at a 1:6 mass ratio of iron to zeolite. 2+ In the solution, under nitrogen protection, the mixture was magnetically stirred for 30 minutes to allow Fe to... 2+ It is fully adsorbed onto the surface and within the pores of the zeolite. Under nitrogen protection, a 0.2 mol / L NaBH4 solution (NaBH4 and Fe) is added dropwise at a rate of 2-3 seconds per drop. 2+ The molar ratio of the reactants was 2:1. The mixture was stirred vigorously, and nitrogen gas was continuously introduced during the reaction for protection. The reaction continued until no more bubbles were generated (approximately 30-60 minutes), and the solution turned black. The solution was washed three times with deionized water and twice with anhydrous ethanol, and then vacuum-dried at 60°C for 12 hours under nitrogen protection to obtain nano-zero-valent iron modified zeolite (Z-nZVI).
[0036] 3. Preparation of carrier slurry Add 8g of polyvinyl alcohol to 100mL of deionized water, heat in a water bath at 80-90℃ and stir until completely dissolved, then cool to 40℃ for later use. Add 1g of sodium alginate to 100mL of deionized water, stir at room temperature until completely dissolved (heating to 50℃ can be used to aid dissolution), and sterilize at 121℃ for 15 minutes. Mix the above PVA solution and SA solution at a volume ratio of 1:1, add 2g of nano-zero-valent iron modified zeolite, and stir thoroughly until uniformly dispersed to obtain the carrier slurry.
[0037] 4. Preparation of bacterial cell embedding solution Cool the carrier slurry to below 35°C, add the compound bacterial solution to the carrier slurry at a volume ratio of 1:5, and gently stir for 5-10 minutes to ensure uniform dispersion of the bacteria, thus obtaining the bacterial encapsulation solution.
[0038] 5. Cross-linking curing Prepare a 3% CaCl2 solution as a cross-linking agent. Load the bacterial cell embedding solution into a syringe and drip it into the cross-linking agent at a rate of approximately 1 drop per 2 seconds. Allow the mixture to stand at 8-12℃ for 12 hours for cross-linking. Remove the cross-linked microspheres and rinse them three times with sterile physiological saline to obtain nano-sized, zero-valent iron-modified immobilized composite bacterial microspheres with a diameter of approximately 3-5 mm. Store at 4℃ for later use.
[0039] Example 2 The difference between this embodiment and Embodiment 1 is that the mass fraction of polyvinyl alcohol in the carrier slurry is 6%, while the other conditions are the same as in Embodiment 1.
[0040] Example 3 The difference between this embodiment and Embodiment 1 is that the crosslinking curing time is 8 hours, while the other conditions are the same as in Embodiment 1.
[0041] Example 4 The difference between this embodiment and Embodiment 1 is that in the nano-zero-valent iron modified zeolite, the mass ratio of iron to zeolite is 1:4, and the other conditions are the same as in Embodiment 1.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that no nano-zero-valent iron modified zeolite is added to the carrier slurry, while the other conditions are the same as in Example 1.
[0043] Comparative Example 2 The difference between this comparative example and Example 1 is that a free complex bacterial community was used for the decolorization experiment, while the other conditions were the same as in Example 1.
[0044] Experimental Example 1 Comparison of decolorization effects of different systems Immobilized microspheres (nZVI-modified immobilized bacterial community) prepared in Example 1, immobilized microspheres (immobilized bacterial community without nZVI) prepared in Comparative Example 1, and free composite bacterial community from Comparative Example 2 were subjected to decolorization experiments under the following conditions: the dye was Reactive Black 5 (RB5), the initial concentration was 100 mg / L, and the dosage was 100 g / L of immobilized microspheres (free bacterial community was calculated based on an equal amount of bacterial cells). The culture was carried out under constant temperature shaking at 30℃ and 150 r / min. Samples were taken at 0, 6, 12, and 24 hours, and the absorbance was measured at 597 nm to calculate the decolorization rate. The experimental results are shown in Table 1.
[0045] Table 1. Comparison of decolorization effects of different systems (Reactive Black 5, 100 mg / L)
[0046] As shown in Table 1, the nZVI-modified immobilized bacterial community in Example 1 achieved a decolorization rate of 94.42% for Active Black 5 after 24 hours, significantly higher than that of Comparative Example 1 and Comparative Example 2. This result indicates that: (1) Immobilization significantly improved the decolorization efficiency of the bacterial community, with Comparative Example 1 showing an increase of 23.5 percentage points compared to Comparative Example 2. This is because the immobilized carrier provides a stable microenvironment and sufficient attachment space for the bacterial community; (2) The addition of nZVI further enhanced the decolorization effect, with Example 1 showing an increase of 15.5 percentage points compared to Comparative Example 1, confirming a significant synergistic effect between the chemical reduction of nZVI and the biodegradation of microorganisms. In the initial stage of the reaction (6 hours), the decolorization rate of Example 1 (58.3%) was close to the 24-hour decolorization rate of Comparative Example 1 (78.9%), indicating that the rapid chemical reduction of nZVI significantly accelerated the decolorization process.
[0047] Experiment Example 2 Decolorization effect under different initial dye concentrations The immobilized microspheres prepared in Example 1 were used to conduct decolorization experiments on Reactive Black 5 solutions of 50, 100, 200, and 500 mg / L, respectively, under the same conditions as in Application Example 1. The decolorization rate was measured after 24 hours. The experimental results are shown in Table 2.
[0048] Table 2 Decolorization effect at different initial dye concentrations
[0049] As shown in Table 2, the decolorization rate gradually decreased with increasing initial dye concentration. Within the low concentration range of 50–100 mg / L, the decolorization rate remained above 94%; when the concentration increased to 200 mg / L, the decolorization rate still reached 87.3%; even at a high concentration of 500 mg / L, the decolorization rate still reached 72.1%. This indicates that the immobilized microspheres prepared in this invention have good dye tolerance and a wide applicable concentration range, which is attributed to the effective protection of the bacterial community by the PVA-SA-zeolite-nZVI composite carrier and the dual-channel synergistic mechanism of nZVI chemical reduction and biodegradation.
[0050] Experimental Example 3 Stability of cyclic use The immobilized microspheres prepared in Example 1 were subjected to a decolorization reaction (Reactive Black 5, 100 mg / L) according to the method in Application Example 1. After each batch reacted for 24 hours, the microspheres were filtered out, washed three times with sterile physiological saline, and then added to fresh dye solution for the next batch of decolorization. A total of 15 batches were carried out. The decolorization rate of each batch was measured after 24 hours. The experimental results are shown in Table 3.
[0051] Table 3. Relationship between the number of batches of immobilized microspheres recycled and the decolorization rate.
[0052] As shown in Table 3, the immobilized microspheres prepared in this invention maintained a decolorization rate of over 90% after 15 batches of repeated use. The decolorization rate decreased by only 4.22 percentage points from 94.42% in the first batch to 90.2% in the 15th batch, a very small decrease. This excellent cyclic stability indicates that: (1) the PVA-SA zeolite composite carrier has good mechanical strength and structural stability, and no significant cracking or disintegration occurred during repeated use; (2) the composite microbial community embedded inside the carrier was effectively protected, and the activity of the microorganisms was maintained during repeated use; (3) the slow iron release characteristic of nZVI ensured its continued chemical reduction effect during multiple batches of use. Good cyclic performance means that the replacement cost of the microbial agent and carrier can be significantly reduced in practical applications.
[0053] Experiment Example 4 Decolorization effect of different dye substrates The immobilized microspheres prepared in Example 1 were used to decolorize 100 mg / L Reactive Black 5 and 100 mg / L Methyl Orange, respectively, under the same conditions as in Application Example 1. The decolorization rate was measured after 24 hours. The values for Reactive Black 5 and Methyl Orange were measured at 597 nm and 464 nm, respectively. The experimental results are shown in Table 4.
[0054] Table 4 Decolorization effect of different dye substrates
[0055] As shown in Table 4, the immobilized microspheres prepared in this invention exhibit good decolorization effects on both azo dyes with different structures. The decolorization rate of Reactive Black 5 after 24 hours is 94.42%, and the decolorization rate of methyl orange after 24 hours is 91.7%. This is attributed to the synergistic effect of the three bacteria in the composite microbial community: Serratia decoloris is responsible for opening the azo chromophore, Bacillus subtilis secretes extracellular enzymes to degrade intermediate products, and Pseudomonas aeruginosa further mineralizes small molecules, enabling the microbial community to have a broad-spectrum degradation ability for azo dyes with different structures.
[0056] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a nano-zero-valent iron-modified immobilized composite microbial community, characterized in that, Includes the following steps: S1. Nano-zero ferric iron is loaded onto zeolite to obtain nano-zero ferric iron modified zeolite; S2. Mix nano-zero-valent iron modified zeolite with polyvinyl alcohol, sodium alginate and water to prepare a carrier slurry; S3. Mix the composite bacterial culture solution with the carrier slurry to obtain the bacterial cell embedding solution; S4. The bacterial cell embedding solution is dropped into a cross-linking agent solution for cross-linking and solidification to obtain immobilized microspheres; The complex microbial community includes Serratia decoloris, Bacillus subtilis, and Pseudomonas aeruginosa. The bacterial suspensions of *Serratia decoloris*, *Bacillus subtilis*, and *Pseudomonas aeruginosa* were mixed at a viable cell count ratio of 1:(0.5-1.5):1; the OD of the mixed bacterial suspension was... 600 It is 0.
7.
2. The preparation method according to claim 1, characterized in that, In the nano-zero-valent iron modified zeolite in S1, the mass ratio of iron to zeolite is 1:
6.
3. The preparation method according to claim 1, characterized in that, In the carrier slurry of S2, the mass fraction of polyvinyl alcohol is 6%~8%, the mass fraction of sodium alginate is 1%, and the mass fraction of nano-zero ferric modified zeolite is 2%.
4. The preparation method according to claim 1, characterized in that, The volume ratio of the composite bacterial culture solution to the carrier slurry in S3 is 1:
5.
5. The preparation method according to claim 1, characterized in that, The crosslinking agent in S4 is a calcium chloride solution with a concentration of 3 wt%.
6. The preparation method according to claim 7, characterized in that, The cross-linking and curing time is 8-12 hours, and the temperature is 8-12℃.
7. The preparation method according to claim 1, characterized in that, The diameter of the immobilized microspheres in S4 is 3~5mm.
8. Nano-zero-valent iron modified immobilized composite microbial community prepared by the preparation method according to any one of claims 1-7.
9. The application of the nano-zero-valent iron modified immobilized composite microbial community as described in claim 8 in dye decolorization.
10. The application according to claim 9, characterized in that, The dye is an azo dye.